Intravascular haemolysis after transcatheter aortic valve implantation with self-expandable prosthesis: incidence, severity, and impact on long-term mortality - Širáková, Andrea; Toušek, Petr; Bednář, František; Línková, Hana; Laboš, Marek; Sulženko, Jakub; Havlíková, Martina; Neuberg, Marek; Kočka, Viktor (European heart journal supplements, 2020)
We aimed to determine the incidence, severity, and long-term impact of intravascular haemolysis after self-expanding transcatheter aortic valve implantation (TAVI). We believe this should be evaluated before extending the indications of TAVI to younger low-risk patients. Prospective, academic, single centre study of 94 consecutive patients treated with supra-annular self-expandable TAVI prosthesis between April 2009 and January 2014. Haemolysis at 1-year post-TAVI was defined per the published criteria based on levels of haemoglobin, reticulocyte and schistocyte count, lactate dehydrogenase (LDH), and haptoglobin. All patients had long-term clinical follow-up (6 years). The incidence of haemolysis at 1-year follow-up varied between 9% and 28%, based on different haemolysis definitions. Haemolysis was mild in all cases, no patient had markedly increased LDH levels. The presence of moderate/severe paravalvular aortic regurgitation was associated with haemolysis (7.7% vs. 23.1%, P = 0.044) and aortic valve area post-TAVI did not differ between groups with or without haemolysis (1.01 vs. 0.92 cm2/m2, P = 0.23) (definition including schistocyte count). The presence of haemolysis did not have any impact on patient prognosis after 6 years with log-rank test P = 0.80. Intravascular haemolysis after TAVI with self-expandable prosthesis is present in 9-28% of patients depending on the definition of haemolysis. The presence of haemolysis is associated with moderate/severe paravalvular aortic regurgitation but not with post-TAVI aortic valve area. Haemolysis is mild with no impact on prognosis.